2003
DOI: 10.1073/pnas.2336107100
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for the metabolism of vitamin D 3 : Unique hydroxylated metabolites formed during catalysis with cytochrome P450scc (CYP11A1)

Abstract: Metabolites of vitamin D3 (D3) (cholecalciferol) are recognized as enzymatically formed chemicals in humans that can influence a wide variety of reactions that regulate a large number of cellular functions. The metabolism of D3 has been extensively studied, and a role for three different mitochondrial cytochrome P450s (CYP24A, CYP27A, and CYP27B1) has been described that catalyze the formation of the 24(OH), 25(OH), and 1(OH) metabolites of D3, respectively. The hormone 1,25-dihydroxyvitamin D3 has been most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
162
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 29 publications
16
162
2
Order By: Relevance
“…However, these levels remained insufficient (data not shown). This finding supports several previous reports which suggested that statins may increase the synthesis of calcitriol by inducing enzyme 7-dechydrocholesterol 23,24 .…”
Section: Chf Patientssupporting
confidence: 93%
“…However, these levels remained insufficient (data not shown). This finding supports several previous reports which suggested that statins may increase the synthesis of calcitriol by inducing enzyme 7-dechydrocholesterol 23,24 .…”
Section: Chf Patientssupporting
confidence: 93%
“…Contrary to drug-metabolizing but similarly to P450s involved in physiological functions, CYP11A1 has narrow substrate specificity-limited to cholesterol, 7-dehydrocholesterol, and vitamin D (6)(7)(8) (Fig. S1 and Table S1).…”
mentioning
confidence: 99%
“…Cholesterol is synthesized from 7-dehydrocholesterol, which is also a precursor of vitamin D 3 . For this reason, we initially observed a statistically significant relation between total cholesterol and vitamin D. HMG-CoA enzyme reductase is key to the synthesis of cholesterol, whereas ultraviolet radiation causes the formation of 25-hydroxyvitamin D. Inhibition of the enzyme may increase levels of 7-dehydrocholesterol and increase the synthesis of 25-hydroxycholecalciferol, thereby increasing vitamin D levels, 10 although we observed no relation between lower cholesterol and increased vitamin D. In addition, 25-hydroxyvitamin D has been shown to inhibit HMG-CoA enzyme reductase activity in in vitro studies. 11 A greater concentration of vitamin D could increase enzymatic inhibition, acting in synergy with the statin in decreasing total cholesterol.…”
Section: Discussionmentioning
confidence: 99%